The Substantive Representation Of Women In The Local Parliament Seats Above 30% - Hayyuning Prastiwi, Juwita; Hendra Wahyudi, Tri; Famelasari, Resya (Opción, 2019)
This study aims to analyze the effectiveness of achieving critical mass on wom- en’s performance in parliament. Using qualitative methodology and in-depth interviews as the main data collection techniques, research and analysis of the functions of legislation and representation in local parliaments are performed. Through representation theory, this research concludes that the achievement of critical mass does not end with critical action. This is because there are no critical female actors who understand the context and wish to fight against the interests of the party and parliament. The statement is influenced by, firstly, socio-political conditions called critical structures which constitute the institu- tional level of political parties and parliament has a dominant role in address- ing issues in parliament. Secondly, the majority of women legislators have less strategic positions, either in political parties or in the structure of the parlia- mentary council. Thirdly, the quality of constituents determines the quality of aspirations, which are substantively often not related to practical or strategic gender needs.